2018
DOI: 10.1124/mol.117.110296
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Biased and Probe-Dependent Signaling at CXC-Motif Chemokine Receptor CXCR3 Induced by Negative Allosteric Modulators

Abstract: Our recent explorations of allosteric modulators with improved properties resulted in the identification of two biased negative allosteric modulators, BD103 (-1-{[3-(4-ethoxyphenyl)-4-oxo-3,4-dihydropyrido[2,3-]pyrimi-din2yl]ethyl}-4-(4-fluorobutoxy)--[(1-methylpiperidin-4-yl)methyl}]butanamide) and BD064 (5-[(-{1-[3-(4-ethoxyphenyl)-4-oxo-3,4-dihydropyrido[2,3-]pyrimidin-2-yl]ethyl-2-[4-fluoro-3-(trifluoromethyl)phenyl]acetamido)methyl]-2-fluorophenyl}boronic acid), that exhibited probe-dependent inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Very recently the molecular basis of biased signaling via G-protein coupled receptors has been uncovered [ 176 ]. As for chemokine receptors, several studies indicate the numerous chemokine receptors among them CCR7, CCR5, and CXCR3 induce biased signaling [ 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 ]. Seven years ago, we have shown that CXCR3 not only induces biased signaling induced by its different ligands, but also that this differential signaling shapes the biological function of effector T cells, and Tr1 cells [ 189 , 190 ].…”
Section: Key Chemokine-chemokine Receptor Interactions That Limit Tumor Growthmentioning
confidence: 99%
“…Very recently the molecular basis of biased signaling via G-protein coupled receptors has been uncovered [ 176 ]. As for chemokine receptors, several studies indicate the numerous chemokine receptors among them CCR7, CCR5, and CXCR3 induce biased signaling [ 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 ]. Seven years ago, we have shown that CXCR3 not only induces biased signaling induced by its different ligands, but also that this differential signaling shapes the biological function of effector T cells, and Tr1 cells [ 189 , 190 ].…”
Section: Key Chemokine-chemokine Receptor Interactions That Limit Tumor Growthmentioning
confidence: 99%
“…In our hands, AMG487 showed no selectivity for G protein activation vs β-arrestin recruitment. 15,16 Over the past 40 years, it has become obvious that G protein-coupled receptors contain alternative binding sites (allosteric sites) where small molecules exert their effects at locations that are topographically distinct from the orthosteric binding site. [17][18][19] Therefore, these allosteric modulators gain therapeutic advantages including greater subtype selectivity and probe dependence.…”
Section: Cxcl11 and Cxcl10 Induce Csc That Is Blocked With Cxcr3 Allomentioning
confidence: 99%
“…Recently, 2 functionally selective negative allosteric modulators were identified that exhibited probe-dependent inhibition of CXCR3 signaling. 15,16 BD064 preferentially inhibits CXCL11-mediated β-arrestin 2 recruitment over G protein activation, whereas BD103 preferably blocks CXCL12-mediated activation of G proteins rather than β-arrestin 2 recruitment. We employed these 2 novel allosteric CXCR3 modulators developed by the Tschammer lab, to determine whether the induction of CSC by CXCL10 or CXCL11 could be blocked.…”
Section: Cxcl11 and Cxcl10 Induce Csc That Is Blocked With Cxcr3 Allomentioning
confidence: 99%
“…Allosteric effects, key mechanisms by which metabolic and cellular pathways are regulated, have revealed promising therapeutic targets . For example, both receptors and ion channels, including G protein‐coupled receptors (GPCR), are vulnerable to inhibition and regulation via allosteric effects . Nucleosome core particle (NCP) structural studies revealed a strong allosteric relationship between RAPTA‐T and AUF, a gold(I) antiarthritic drug that is being repurposed as an anticancer drug .…”
Section: Figurementioning
confidence: 99%